2015
DOI: 10.1002/pc.23668
|View full text |Cite
|
Sign up to set email alerts
|

Banana/sisal fibers reinforced poly(lactic acid) hybrid biocomposites; influence of chemical modification of BSF towards thermal properties

Abstract: The present work focused on thermal behavior of biocomposites based on poly(lactic acid) (PLA) reinforced with untreated and benzoyl peroxide (BP) treated banana/sisal fibers (BSF) combination. Fabrication of biocomposites was performed by extrusion followed by injection molding. Fourier transformed infrared (FTIR) spectral technique ascertained the nature of bonding between BSF and PLA. The thermal properties of virgin PLA, UT‐BSF/PLA, and BP‐T‐BSF/PLA composites were studied by DSC and TGA analysis. DSC anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Likewise, the pre‐treatment of heat and pectinase enzymes also improved a significant amount in the degree of crystallinity from 32.3 ± 0.5 and 35.5 ± 0.7%, respectively. Equally, surface treatments can also help to align the microfibrous structures of cellulose and improve the crystalline nature of the fibers which all present an equivalent contribution to the ramie fibers/PLA biocomposite crystallinity level .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the pre‐treatment of heat and pectinase enzymes also improved a significant amount in the degree of crystallinity from 32.3 ± 0.5 and 35.5 ± 0.7%, respectively. Equally, surface treatments can also help to align the microfibrous structures of cellulose and improve the crystalline nature of the fibers which all present an equivalent contribution to the ramie fibers/PLA biocomposite crystallinity level .…”
Section: Resultsmentioning
confidence: 99%
“…For thermal properties, the thermal annealing process of ramie fibers reinforced PLA polymer composite involving heat treatment (above its crystallization temperature) is known to impart relaxation capability in PLA‐based polymer systems . Nassiopoulos and Njuguna and Suryangegara et al both reported the improved thermo‐mechanical behavior of reinforced PLA composites with tunable and desirable properties courtesy of heat annealing along with the degree of crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of natural fiber-reinforced thermoplastic composites were improved as a result of the incorporation of natural fiber with relatively high strain. Asaithambi et al [138,139] studied the mechanical properties of hybrid banana/sisalreinforced polylactic acid composite. Compared to banana-reinforced Poly(lactic acid) (PLA) and neat PLA, improved mechanical properties were observed in the composites incorporated with high-strength sisal fiber with banana fiber-PLA composite.…”
Section: Mechanical Properties Of Hybrid Compositementioning
confidence: 99%
“…Several studies have shown that the mechanical properties of a composite are strongly related to the matrix nature, fiber morphology, aspect ratio, fiber–matrix interface quality, as well as fiber type, concentration and orientation distribution . For example, the fibers in a thin plate tend to orient parallel to the flow direction near the walls due to shear stresses, while they tend to align perpendicular to the flow in the central zone .…”
Section: Introductionmentioning
confidence: 99%